Cultural Aspects of Merarik Kodeq as Risk Factors f or LBW Incidents - Asri Qurrota Aini (Poltekkes Kemenkes Mataram, 2026)
Background: Low birth weight (LBW) remains a maternal and child health problem that contributes to increased neonatal mortality rates, including in West Lombok Regency. In addition to medical factors, sociocultural aspects such as merarik kodeq are thought to play a role as risk factors. This study aims to analyze the relationship between the cultural aspect of merarik kodeq and the incidence of LBW in the working areas of the Kediri and Banyumulek Community Health Centers in West Lombok Regency, West Nusa Tenggara Province. Research Methods: This study used an analytical observational design with a case-control approach. A sample of 74 respondents was selected using simple random sampling, consisting of 37 case groups (LBW) and 37 control groups (non-LBW). Data were collected through interviews using a validated questionnaire and maternal and child health (MCH) records. Data analysis was performed using bivariate analysis with the chi-square test at a significance level of 0.05 and calculation of the odds ratio (OR). Research Results: The results showed a significant relationship between gestational age at delivery and LBW (p=0.001; OR=3.467). In addition, there was a significant relationship between the mother's age at marriage (merarik kodeq) and LBW (p=0.001; OR=6.481). Mothers who married at <19 years of age had a greater risk of giving birth to LBW babies than those who married at the ideal age. Meanwhile, the mother's age at pregnancy did not show a significant relationship with LBW (p>0.05). Conclusion: The cultural aspect of codeq is one of the risk factors for LBW in West Lombok Regency, West Nusa Tenggara Province.